SINKRONISASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 DENGAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - ', Elsa Aprilia; ', Anjar Sri Ciptorukmi Nugraheni; ', Luthfyah Trini Hastuti (Jurnal Privat Law, 2019)
AbstractThe writing of this article aims to synchronize The Judgment Of Mahkamah Konstitusi he knows no. 46/PUU-VIII/2010 with law number 1 Year 1974 about marriage. This type of research using normative legal research is descriptive and the approach used approach to legislation. Legal research materials used are primary and secondary legal materials, the techniques used in the collection of the material law in this research is the study of librarianship or study document. This research uses the legal materials analysis techniques with methods that use syllogisms deductive thinking patterns. There are several provisions in The Judgment Of Mahkamah Konstitusi No. 46/PUU-VIII/2010 that are not in sync with the law number 1 Year  1974  about  marriage  as  arrangement  about  children,  relation  of  children  outside  marriage, responsibility from parent and authentication children in understanding The Judgment Of Mahkamah Konstitusi not synchron with the notion of legitimate son in law Marriage, but there is also a provision that such provision of synchronous’s authentication that protection about children outside marriage . After there is proof about the relationship of blood must remain an endorsement done his father against son beyond mating to be legitimate children.Keywords: Synchronization; Children Outside Of Marriage; The Judgment Of Mahkamah KonstitusiAbstrakPenulisan  artikel  ini  bertujuan  untuk mengetahui sinkronisasi Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 dengan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan. Jenis penelitian menggunakan  penelitian  hukum  normatif  yang  bersifat  deskriptif  dengan  pendekatan  perundang-undangan. Bahan penelitian hukum yang digunakan adalah bahan hukum primer dan sekunder, teknik yang digunakan dalam pengumpulan bahan hukum adalah studi kepustakaan atau studi dokumen. Teknik analisis memakai bahan hukum dengan metode silogisme yang menggunakan pola berpikir deduktif. Terdapat beberapa ketentuan dalam Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 yang tidak sinkron dengan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan seperti hubungan anak luar kawin, pembuktian anak dan tanggung jawab orangtua, namun terdapat juga ketentuan yang sinkron seperti ketentuan tentang pengaturan yang memberi perlindungan terhadap anak luar kawin. Setelah ada pembuktian tentang hubungan darah harus tetap ada pengesahan yang dilakukan ayahnya terhadap anak luar kawin agar menjadi anak sah.Kata kunci: Sinkronisasi; Anak Luar Kawin; Putusan Mahkamah Konstitusi.